Lack of skills or formal qualifications? New evidence on cross-country differences in the labor market disadvantage of less-educated adults - Jan Paul Heisig; Maurice Gesthuizen; Heike Solga (Social Science Research, 2019)
We use PIAAC data on the literacy and numeracy skills of 49,366 25-to-54-year-olds in 27 countries to shed new light on cross-national variation in the labor market disadvantage of less-educated adults (i.e., those who have not completed upper secondary education). Our empirical analysis focuses on the occupational status gap between less-educated adults and those with a degree at the upper secondary level and yields three main findings. First, individual-level differences in literacy and numeracy skills are an important source of cross-national variation in labor market inequalities by educational attainment, but substantial gaps in occupational status remain even after accounting for individuals' actual skills and further socio-demographics. Second, this remaining occupational status gap rises with a country's level of “skills transparency” (i.e., the extent to which formal qualifications are more informative about actual skills): labor market gaps increase as the skills gap between the two educational groups increases and as the within-group distribution of skills becomes more homogeneous. Third, country differences in skills transparency seem to be the primary mediating channel for the inequality-enhancing effect of tracking in secondary education found in previous research.
Keywords: 330; education; inequality; social stratification; international comparison; skills; PIAAC